Carcinoid heart disease involving the left heart: a case report and biomarker analysis. (8th January 2019) - Lichtenauer, Michael; Pichler, Tristan; Eder, Sarah; Mirna, Moritz; Magnes, Theresa; Wernly, Bernhard; Paar, Vera; Jung, Christian; Prinz, Erika; Seitelberger, Rainald; Hoppe, Uta C.
Abstract: Herein, we report the case of a 67‐year‐old woman who was admitted to our hospital because of dyspnoea and oedema of the lower extremities. Transthoracic echocardiography revealed severe tricuspid and mitral regurgitation, and the leaflets of the tricuspid valve were found to be rigid and almost immobile. The plasma concentrations of serotonin and chromogranin A were elevated, and hence, suspicion for carcinoid heart disease was raised. In addition to the diagnostic workup and medical and surgical treatment, we analysed levels of novel cardiovascular biomarkers throughout the entire follow‐up by means of enzyme‐linked immunosorbent assay. A dopa positron emission tomography (DOPA‐PET) was conducted and showed a neoplasm in the terminal ileum. Tricuspid valve replacement, mitral valve repair, and a closure of the patent foramen ovale (PFO) were conducted. Two months later, hemicolectomy and liver segment resection were performed. The tumour was resected, and the diagnosis of a neuroendocrine tumour (NET) was confirmed. Throughout the follow‐up, we observed a decrease in the plasma levels of novel biomarkers [e.g. interleukin‐8 (IL‐8), soluble suppression of tumorigenicity‐2 (sST2), and heart‐type fatty acid‐binding protein (H‐FABP)] over the follow‐up period. In our case, carcinoid heart disease resulted in a severe tricuspid regurgitation as commonly seen in these patients. Moreover, a pre‐existent mitral regurgitation was likely aggravated by fibrotic remodelling, because a PFO has led to a right‐to‐left shunt and might have caused left heart involvement. As IL‐8 was associated with adverse outcomes in patients with NETs, and sST2 and H‐FABP were associated with adverse outcomes in patients with heart failure previously, these biomarkers could aid in the risk stratification of patients with NET.